Altered gut microbiota-host bile acid metabolism in IBS-D patients with liver depression and spleen deficiency pattern - Liqing Du; Zhaozhou Zhang; Lixiang Zhai; Shujun Xu; Wei Yang; Chunhua Huang; Chengyuan Lin; Linda L. D. Zhong; Zhaoxiang Bian; Ling Zhao (BMC, 2023)
Abstract Background Dysregulation of gut microbiota-host bile acid (BA) co-metabolism is a critical pathogenic factor of diarrhea-predominant irritable bowel syndrome (IBS-D). Traditional Chinese Medicine (TCM), instructed by pattern differentiation, is effective in treating IBS-D, in which liver depression and spleen deficiency (LDSD) is the most prevalent pattern. Still, it is unclear the linkage between the LDSD pattern and the BA metabolic phenotype. Purpose This study aimed to uncover the biological basis of the LDSD pattern from the BA metabolic perspective. Methods Patients with IBS-D completed questionnaires regarding the irritable bowel severity scoring system (IBS-SSS), stool frequency, Stool Bristol scale, and Self-Rating Scales of mental health. Fasting blood and morning feces were collected to analyze the gut metagenome and BA-related indices/metabolites. Results IBS-D patients with LDSD had a higher incidence of BA overexcretion (41% vs. 23% non-LDSD) with significant elevations in fecal total BAs and serum BA precursor 7α-hydroxy-4-cholesten-3-one levels. Compared to controls or non-LDSD patients, LDSD patients had a featured fecal BA profile, with higher proportions of deoxycholic acid (DCA), 7-ketodeoxycholic acid, and lithocholic acid. It is consistent with the BA-metabolizing genomic changes in the LDSD gut microbiota characterized by overabundances of 7-dehydroxylating bacteria and BA-inducible genes (baiCD/E/H). The score of bowel symptoms (stool frequency and abdominal pain) showing greater severity in the LDSD pattern were positively correlated with bai-expressing bacterial abundances and fecal DCA levels separately. Conclusion We clarified a differed BA metabolic phenotype in IBS patients with LDSD, which closely correlates with the severity of bowel symptoms. It demonstrates that gut microbiota and host co-metabolism of BAs would provide crucial insight into the biology of the LDSD pattern and its internal relationship with IBS progression.